STRATEGI KOMUNIKASI LINTAS BUDAYA KONSULTAN PUBLIC RELATIONS PERUSAHAAN MINYAK DAN GAS BUMI DALAM MENGHADAPI PERBEDAAN BUDAYA PADA PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY - Tikka Muslimah (JURNAL PURNAMA BERAZAM, 2023)
Public relations activities in a company can be carried out by a public relations consultant. Public relations consultants have the same duties and functions as public relations from a division of a company. Oil and gas companies owned by the government in Indonesia also use public relations consultants who are focused on implementing CSR programs. Despite using a public relations consultant, this oil and gas company has received many awards for its achievements in the field of CSR. In the program implementation process, public relations consultants face cultural differences from the various areas that are the program's targets. But the public relations consultant must have a strategy in dealing with these differences. This research uses a qualitative approach with the case study method. The results of this study indicate that each region has different cultural constraints. There are different characteristics between Javanese and Papuan people as recipients of the CSR program. So that the public relations consultant must adjust the way of communicating a program, namely in Low Context or High Context. In addition, the public relations approach used by CSR practitioners is a collaborative approach.